Awareness of and subjective needs for post-discharge healthcare services among older adult patients - Hsin-Yen Yen; Doresses Liu; Mei-Ju Chi; Hao-Yun Huang (BMC, 2023)
Abstract Background Increasing patient awareness of post-discharge care resources is an effective strategy to reduce rehospitalization rates and medical costs. Therefore, the purpose of this study was to explore hospitalized older adult patients' awareness of and subjective demands for post-discharge healthcare services. Methods A cross-sectional study design was conducted from November 2018 to May 2020. STROBE statement was completed. Participants were inpatients over 65 years of age in the general ward of a medical center in northern Taiwan. A questionnaire was used to collect data by face-to-face interviews. Two hundred and twelve participants were recruited. Home nursing care, home rehabilitation, home respiratory therapy, home services, assistive devices rental, and transportation were the main post-discharge healthcare services in this study. Results Overall, 83.5% of older adult patients were aware of and 55.7% of the older adult patients demanded at least one post-discharge healthcare services. Logistic regression results found that, patients experiencing moderate to severe disability and cognitive impairment, and those hospitalized in the past year had significantly higher demands for services. Conclusions Developing post-discharge healthcare services for older adult patients provides continuous patient-centered services for assisting patients and their families in adapting to the transition period of the post-acute stage. Satisfying these demands is beneficial for older adult patients and their families, as well as for reducing readmissions and medical costs.